PENGARUH KOMPENSASI TERHADAP KINERJA KARYAWAN KOPERASI SAWIT KARYA BHAKTI MAHATO - Armansyah Armansyah; Yuritanto Yuritanto; Marsudi Marsudi (Jurnal Inovasi Penelitian, 2021)
Human resources have a vital role in a company. All aspects related to resources ultimately also affect performance. In terms of Employee Performance, in this study the authors focus on Employee Compensation and Performance. This study aims to see empirically the effect of compensation on employee performance at the Koperasi Sawit Karya Bhakti Mahato Mahato Village, North Tambusai District. This study used 25 employees as respondents who were used as samples. The technique of using data uses online questionnaires that are sent to respondents. The data obtained were analyzed using Linear Regression analysis. The results obtained indicate a positive influence and variable compensation on employee performance.